Cell-Free and Yeast-Based Production of the Malarial Lactate Transporter, PfFNT, Delivers Comparable Yield and Protein Quality - Hajek, Philipp; Bader, Annika; Helmstetter, Folknand; Henke, Björn; Arnold, Philipp; Beitz, Eric (Frontiers in Pharmacology, 2019)
Cell-free protein production is an attractive alternative to cell-based expression. Rapid results, small-volume reactions, irrelevance of protein toxicity, flexibility and openness of the system are strong points in favor of the cell-free system. However, the in vitro situation lacks the cellular quality control machinery comprising e.g. the translocon for inserting membrane proteins into lipid bilayers, and chaperon-assisted protein degradation pathways. Here, we compare yield and protein quality of the lactate transporter, PfFNT, from malaria parasites when produced in Pichia pastoris yeast, or in an Escherichia coli S30-extract-based cell-free system. Besides solubilization and correct folding, PfFNT requires oligomerization into homopentamers. We assessed PfFNT folding/oligomerization and function by transmission electron microscopy imaging, transport assays, and binding of small-molecule inhibitors. For the latter, we used chromatography of the PfFNT-inhibitor complex with dual-wavelength detection, and biolayer interferometry. Our data show, that PfFNT possesses an intrinsic capability for assuming the correct fold, oligomerization pattern, and functionality during in vitro translation. This competence depended on the detergent present in the cell-free reaction. The choice of detergent further affected purification and inhibitor binding. In conclusion, in the presence of a suitable detergent, cell-free systems are very well capable of producing high quality membrane proteins.